Pautas de crianza y desarrollo socioafectivo en la infancia (2010)
This article presents a revision and reflexions on the relation between the parenting styles and the socioaffective development during childhood, as a result of the research done and assuming that the mental health of the parents, the upbringing guidelines and the socioaffective development of children are very related and that the socioaffective development of these change according to a great number of evolutive and contextual variables. Finally, it is considered that the family is very important in order to facilitate the development of prosocial behaviours, the emotional self regulation and for preventing mental health problems during the childhood such as depression, aggressiveness, low self esteem, anxiety and others.